Teachers' strategies for training students' literacy and numeracy through media-based learning in Pansor Village - Eliyana, Eliyana; Sapriadi, Sapriadi; Atnika, Atnika; Risnawati, Risnawati; Juliadi, Juliadi; Saputra Nur, Beni Edi; Imron, Dedi; Purnama, Dimas; tami, Ayu Nurhasni; Rahmatin, Mulkia (Jurnal Ilmiah Mandala Education (JIME), 2024)
This community service is entitled teacher strategies in training students' literacy and numeracy through media-based learning at SDN 5 in Pansor village, Kayangan sub-district, North Lombok district. This service is carried out with several objectives, first, to increase awareness about the importance of learning numeracy literacy from an early age, second, to provide knowledge to the students of SDN 5 Sesait that learning numeracy literacy is not just by reading books but can use several tools. apart from books such as drawing media and ice cream sticks and so on. The method used is a face-to-face and direct practice method of learning literacy and numeracy using image-based media or using ice cream sticks by constructing a framework. The results obtained from this service or socialization are to outline the methods used by teachers to teach students mathematics and literacy using media-based learning. Numeracy literacy is one of the first steps or stages that must be trained in school.  One of the factors causing media-based Literacy and Numeracy training to be held in Pansor Village, especially at SDN 5 Sesait, is the low ability in reading and arithmetic in grades 5 and 6 which is caused by contemporary factors, namely playing online games and playing social media, especially for children. elementary school children who are continuously without parental supervision.